Fasilitasi Masyarakat untuk Meningkatkan Minat Belajar Membaca Al-Quran melalui BBQ Metode ’Usmani di Desa Wagir Kidul - Mohammad Agus Fatkhur Rohman; Fuad Fitriawan (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The majority of the community in Wagir Kidul practices Islam, but there are still many who have not been touched by Quranic reading education. The aim of this community service is to enhance the interest in learning to read the Quran among the residents of Wagir Kidul village Pulung Ponorogo, Indonesia. The method employed in this community service is the Asset Based Community-Driven Development (ABCD) approach, consisting of five implementation stages: Inculturation, Discovery, Design, Define, and Reflection. The result of this community service is the implementation of the Quran Reading Development (BBQ) program using the 'Usmani' method, with two face-to-face sessions every week, totaling five sessions. The program had 42 participants from the Wagir Kidul community, including junior high school students to the elderly, in the fifth session. The follow-up plan for this community service is to continue the Quran Reading Development (BBQ) program until completing the recitation of eight books, which is estimated to take approximately nine months. Mayoritas masyarakat Wagir Kidul beragama Islam tetapi masih banyak yang belum tersentuh pendidikan baca Al-Qur’an. Tujuan dari pengabdian masyarakat ini adalah untuk meningkatkan minat belajar membaca Al-Qur’an pada masyarakat desa Wagir Kidul Pulung Ponorogo, Indonesia. Metode yang digunakan pada pengabdian masyarakat ini adalah metode Asset Based Community-Driven Development (ABCD) dengan lima tahap pelaksanaan yaitu; Inkulturasi, Discovery, Design, Define, dan Refleksi. Hasil dari pengabdian masyarakat ini adalah terlaksananya Bina Baca Al-Qur’an (BBQ) Metode ’Usmani dua kali tatap muka setiap minggunya dengan jumlah pertemuan sebanyak lima kali dengan peserta masyarakat Wagir Kidul usia SLTP sampai lansia sebanyak 42 peserta pada pertemuan kelima. Rencana tindak lanjut terhadap pengabdian masyarakat ini adalah BBQ dilanjutkan sampai khatam delapan buku, waktu yang dibutuhkan kurang lebih sembilan bulan.